Combination chemoprophylaxis and immunoprophylaxis in reducing the incidence of leprosy - Duthie MS; Balagon MF (Dove Medical Press, 2016)
Malcolm S Duthie,1 Marivic F Balagon2 1Infectious Disease Research Institute, Seattle, WA, USA; 2Cebu Skin Clinic, Leonard Wood Memorial Center for Leprosy Research, Cebu City, the Philippines Abstract: Leprosy is a complex infectious disease caused by Mycobacterium leprae that is a leading cause of nontraumatic peripheral neuropathy. Current control strategies, with a goal of early diagnosis and treatment in the form of multidrug therapy, have maintained new case reports at ~225,000 per year. Diagnostic capabilities are limited and even with revisions to multidrug therapy regimen, treatment can still require up to a year of daily drug intake. Although alternate chemotherapies or adjunct immune therapies that could provide shorter or simpler treatment regimen appear possible, only a limited number of trials have been conducted. More proactive strategies appear necessary in the drive to elimination. As a prevention strategy, most chemoprophylaxis campaigns to date have provided about a 2-year protective window. Vaccination, in the form of a single bacillus Calmette–Guérin (BCG) immunization, generally provides ~50% reduction in leprosy cases. Adapting control strategies to provide both chemoprophylaxis and immunoprophylaxis has distinct appeal, with chemoprophylaxis theoretically buttressed by vaccination to generate immediate protection that can be sustained in the long term. We also discuss simple assays measuring biomarkers as surrogates for disease development or replacements for invasive, but not particularly sensitive, direct measures of M. leprae infection. Such assays could facilitate the clinical trials required to develop these new chemoprophylaxis, immunoprophylaxis strategies, and transition into wider use. Keywords: mycobacteria, treatment, antibiotics, T-cell, vaccine, prevention Hansen's disease